Isolasi dan Identifikasi Jamur Endofit Tanaman Manggis (Garcinia mangostana L.) - Iva Akmalasari; Endang Sri Purwati; Ratna Stia Dewi (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
Mangosteen (Garcinia mangostana L.) is one of Indonesia's tropical horticultural commodities with high economic value. Mangosteen also has a lot of functions such as a producer of a wide variety of functional compounds such as anticancer, antiviral, antibacterial and antifungal that have some bioactive component i.e., micotoxin, enzyme, and antibiotics. The research was carried out to investigate the endophyte fungi in mangosteen plant tissue. Endophyte fungal isolation from mangosteen plant tissue resultsed 11 isolates which have identified Phoma sp., Acremonium sp., 2 isolates of Penicillium sp., Geotrichum sp., Pestalotiopsis sp., Botryosphaeria sp., Colletotrichum sp., Chrysosporium sp., Aspergillus sp. and Blastomyces sp., and 2 isolates have not been identified.